A Typo-Morphological Analysis to Trace the Historical Transformation of Urban Blocks Around Ramna Race Course Between 1947-200 - Afzal, Farhat (International Planning History Society Proceedings, 2024)
Due to negligence in planning and deficient urban governance, Dhaka city ranks very low in various liveability indexes and global surveys carried out annually. Unlike Chandigarh or Islamabad, the city was not developed with the guidance of renowned and established city planners. And yet, its physical characteristics have been gradually transforming over the past 400 years. This raises the question, how is that transformation happening over the course of time, and what are the causes? To understand this, this paper aims to look at the transformation of Ramna, one of the historically and politically significant neighbourhoods of Dhaka. The paper focuses on typo morphological analysis of urban blocks in and surrounding the area formerly known as Ramna Race Course, between the time period 1947 and 2000. Using typo morphological analysis, this study identified the main reasons for the transformation of some selected parts of the area in and surrounding the Ramna Race Course area. The results show that power play by political parties, development to support institutional needs of University of Dhaka and encroachment by newer buildings are the primary reasons for the transformation of the six selected study areas.